Subjective discomfort model of the micro commercial vehicle vibration over different road conditions. (February 2019) - Huang, Yu; Li, Dou
Abstract: Vibration is a main environmental stress in vehicles. The discomfort caused by vibration may differ in different vehicles and road conditions. This laboratory study investigated the discomfort caused by the vibration of 3 models of micro commercial vehicles running in 4 types of road conditions (i.e., the asphalt, concrete, gravel and bump road). Thirty participants judged the subjective discomfort caused by 72 whole-body vibration stimuli with the W k weighted root-mean-square (r.m.s.) accelerations ranging from 0.531 to 2.991 ms −2 using the absolute magnitude estimation method. Results showed that at the same acceleration, especially at relatively great accelerations (>1.5 ms −2 ), vibration containing more high-frequency components (>20 Hz) caused greater discomfort than those containing less high-frequency components. Different discomfort models of vibration and different equivalent comfort contours between noise and vibration in various vehicles and road conditions were determined. The discomfort models would predict the discomfort from the r.m.s. accelerations of whole-body vibration (together with vibration in hand and foot) accurately, and the equivalent comfort contours would help to make a targeted improvement of noise and vibration.